Amy and friends: improving the lives of individuals affected by DNA repair disorders - Hughes, Jayne; Orioli, Donata; Arseni, Lavinia (FEBS letters, 2025)
DNA repair disorders are rare genetic conditions characterized by defects in the mechanisms responsible for repairing damaged DNA. DNA damage occurs frequently due to environmental factors, and in healthy cells, repair systems fix this damage to maintain genomic integrity. In individuals with DNA repair disorders, these mechanisms are impaired, leading to accumulated damage, cellular dysfunction, premature aging, and cell death. Symptoms vary depending on the specific repair pathway defect, with examples including Cockayne syndrome (CS), trichothiodystrophy (TTD), and xeroderma pigmentosum. Amy and Friends was founded by Jayne Hughes in the UK in 2007 to support children/young adults and families suffering from CS, TTD, and linked DNA repair disorders. In this second of a new series on patient advocacy, FEBS Letters interviews Founder and CEO Jayne Hughes and molecular geneticist and specialist team member Prof. Donata Orioli on the aims, achievements, and activities of Amy and Friends.
Online verfügbar: 06. Mai 2025
Gesehen am 17.10.2025